Field Test of a MESL (Membrane-Enveloped Soil Layer) Road Section in Central Alaska - Smith, North; Pazsint, Daniel A. (1975)
The MESL (Membrane-Enveloped Soil Layer) concept for using fine- grained soil as a structural embankment for expedient military uses was tested in a subarctic environment over two freeze-thaw seasons. The encapsulated silt was placed at a moisture content of approximately 4.5% below the optimum of 17. 5% for the CE-12 compaction effort. Non-woven polypropylene membrane with CRS-2 emulsified asphalt was used as a waterproofing agent for both the bottom and top membranes. The emulsion was hand-applied with roofing cement brushes to simulate a remote tactical situation. The test section had dimensions of approximately 200 by 20 by 2-1/2 ft and had a sand surfacing about 1-1/2-in. thick. The north end of the section, which was undamaged by snow removal equipment, withstood over 500 traffic passes of a loaded military dump truck having a gross weight of nearly 9 tons during the second and third spring thaw seasons without major rutting.